Ecosystem carbon storage and carbon metabolizing microorganisms in three types of grasslands on the Qinghai-Tibet Plateau - Qian Liu; Wenquan Yang; Jiancun Kou; Qinyao Li; Yangcan Zhang; Xilai Li; Jing Zhang; Zhiting Hao; Lu Chi; Yuze Ning (Frontiers in Microbiology)
BackgroundThe response of soil microorganisms to environmental changes can affect the storage and stability of carbon pools in ecosystems. However, the intrinsic link between the structure of soil carbon-metabolizing microbial communities and their roles in different types of alpine grasslands remains unclear.MethodsThis study explores how carbon storage varies among alpine meadow (AM), alpine wetland (AW), and alpine desert (AD) on the Qinghai-Tibet Plateau and assesses the influence of a wide range of soil microbial and vegetation factors, so as to identify microbial predictors of ecosystem carbon storage. The study revealed four types of carbon metabolizing microbial communities responded to changes in vegetation types and their impact on the storage and stability of carbon pools.ResultsThe carbon storage of three grassland types followed the relativity of AW > AM > AD. Soil water content (SWC) was identified as the major factor affecting the carbon storage of grassland ecosystems by increasing vegetation belowground biomass and soil total carbon content, directly or indirectly influencing the diversity of four types of soil microorganisms through its effects on soil physicochemical properties. The community structure of these four types of carbon metabolizing microorganisms in AW significantly differed from that of AM and AD. The diversity of carbon-fixing microorganisms significantly reduced ecosystem carbon storage to a great extent. The relative abundance of carbon-fixing microorganisms Thiobacillus, Mesorhizobium, Azospirillum, and Methylibium significantly increased grassland carbon storage, while the relative abundance of chitinase-producing microorganisms Cellulomonas and Stenotrophomonas significantly decreased it.